a = 3, b= - 4 and c = - 4
expand the left side using FOIL
(2x + 1)(ax + b) = 2ax² + 2bx + ax + b = 2ax² + x(2b + a) + b
compare the coefficients of expressions on left and right sides.
compare 2ax² + x(2b +a) + b with 6x² - 5x + c
coefficients of x² terms → 2a = 6 ⇒ a = 3
coefficients of x terms → 2b + a = - 5 → 2b + 3 = - 5 → 2b = - 8 ⇒ b = - 4
constant terms c = b = - 4
Answer:
60π
Step-by-step explanation:
If the circle has radius of 30 units, substitute r=30 into the formula C = 2πr.
C = 2π(30)
C = 60π
Answer:
18√3
Step-by-step explanation:
tan Ф = opposite/adjacent
tanФ = AB/AC
tan 60 = AC/AB
Tan 60 =√3 AB=18
√3=AC/18
AC=18√3
Answer:
0.25, 4/16, theres like a million more
Step-by-step explanation:
is that what youre looking for?
Answer: -5 < x < 6. (-5, 6)
Step-by-step explanation: